Innovative events - Max Nathan; Anna Rosso (University of Birmingham, Birmingham Business School, 2019)
We take a fresh look at firms' innovation-productivity linkages, using novel data capturing new aspects of innovative activity. We combine UK administrative microdata, media and website content to develop experimental metrics - new product/service launches - for a large panel of SMEs. Extensive validation and descriptive exercises show that launches complement patents, trademarks and innovation surveys. We also establish connections between launches and previous innovative activity. We then link IP, launches and productivity, controlling for media exposure and firm heterogeneity. Launch activity is associated with higher SME productivity, especially in the service sector. High-quality launches and medium-size firms help drive this result.
Keywords: C55; L86; O81; 330; innovation; productivity; ICT; data science